Aortic arch variant presenting as an acute ST elevation myocardial infarction. (10th January 2013) - Alirhayim, Zaid; Qureshi, Waqas; Shafiq, Ali; Hassan, Syed
Abstract : A woman in her 40s presented to our institution with a first episode of sudden-onset right-sided chest pain. Initially, her ECG revealed ST segment elevation in leads V1–V3 and cardiac biomarkers were elevated with a troponin I (TnI) 5 µg/l. Her cardiac risk factors included type II diabetes mellitus and a history of hypertension. Intravenous heparin was initiated and emergent cardiac catheterisation revealed non-obstructive coronary artery disease. A two-dimensional echocardiogram confirmed hypokinesis of the anterior wall. A CT thorax demonstrated a rare anatomical variant of the aortic arch with an aberrant right subclavian artery. This is a rare case of an aortic arch anomaly presenting as a myocardial infarction.